2022
DOI: 10.3389/fmicb.2022.1036091
|View full text |Cite
|
Sign up to set email alerts
|

Differentially enriched fungal communities in root rot resistant and susceptible varieties of tobacco (Nicotiana tabacum L.) under continuous monoculture cropping

Abstract: Root rot is a major disease of tobacco that causes crop losses of up to 15–20% of global tobacco production. The present study aimed to compare the fungal communities, and physicochemical properties of rhizosphere soil of root rot resistant (Yunyan 87; Y) and susceptible (Honghua Dajinyuan; H) tobacco varieties. Four treatments of each variety under continuous monocropping cultures included: control groups (HT0 and YT0); 2 years of continuous cropping (HT2 and YT2); 4 years of continuous cropping (HT4 and YT4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Tobacco black shank disease was the main soil borne disease in the region and the word and it outbreaked at high temperature and high humidity condition(Mid-to-late July in Baishui). So a total of 250 plants from each treatment were investigate according to Ao et al (2022) . We conducted surveys every 5 days throughout July 2020 and subsequently calculated the average incidence rate according to the formula.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco black shank disease was the main soil borne disease in the region and the word and it outbreaked at high temperature and high humidity condition(Mid-to-late July in Baishui). So a total of 250 plants from each treatment were investigate according to Ao et al (2022) . We conducted surveys every 5 days throughout July 2020 and subsequently calculated the average incidence rate according to the formula.…”
Section: Methodsmentioning
confidence: 99%
“…It is widely considered that soil nutrient imbalances, disruption of microbial communities, and allelopathic autotoxicity are the most important factors for continuous cropping challenges ( Deng et al., 2017 ; Bai et al., 2019 ; Ao et al., 2022 ). Allelochemicals, a form of root exudates, play direct ( Bortolo et al., 2018 ) or indirect ( Ren et al., 2017 ) roles in consecutive monoculture problems.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of root rot infection in P. volubilis After inoculating the six fungal isolates into P. volubilis seedlings, we assessed disease infection degree by looking at disease incidence (DI) and disease severity (DS). The DI was assessed as the percentage of infected seedlings out of the total of all treated seedlings for each fungus (Ao et al 2022 ) as shown in the following formula:…”
Section: Pathogenicity Test Of Fungal Isolatesmentioning
confidence: 99%